SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN PENGOBATAN TRADISIONAL KARDIOVASKULAR MENGGUNAKAN METODE SMART - Syabaniah, Rifa Nurafifah; Marsusanti, Eva; Nugraha, Rusli; Yulistria, Resti (Simetris: Jurnal Teknik Mesin, Elektro dan Ilmu Komputer, 2023)
Penyakit kardiovaskular merupakan penyakit gangguan pada jantung dan pembuluh darah. Jenis pengobatan kardiovaskular sangat beragam, sebagian masyarakat termasuk masyarakat wilayah Kota cianjur mempercayai pengobatan tradisional dapat mengobati dan mengurangi resiko penyakit kardiovaskular. Metode penelitian pada penelitian ini Cardiovascular disease is a disease of the heart and blood vessels. Types of cardiovascular treatment are very diverse, some people including the people of the city of Cianjur believe that traditional medicine can treat and reduce the risk of cardiovascular disease. The research method in this study was observation and interviews with the administration of registration of patients with traditional medicine and patients with cardiovascular disease in several places of traditional medicine in the city of Cianjur. The selection of traditional medicine for cardiovascular patients uses the SMART decision-making system method with four alternatives, namely: Repleksi, Leech, Gurah and acupuncture. The result of the calculation of the SMART method for selecting the right traditional medicine for cardiovascular patients is the traditional leech treatment. This is evident from the results of the calculation of the utility value of 81.45 as the largest utility value of the four alternatives.